2012
DOI: 10.1111/j.1467-6494.2011.00753.x
|View full text |Cite
|
Sign up to set email alerts
|

To Discover or to Create: Metaphors and the True Self

Abstract: Three studies examined how endorsement of self-discovery and self-creation metaphors influences belief in the true self and its use as meaning source. It was hypothesized that discovery metaphors contribute to belief in the true self and bolster the relationship between true self-knowledge and meaning. Study 1 supported the hypothesis that discovery is positively associated with belief in the true self among a sample of college students (N = 311). Studies 2 and 3 extended the analysis by showing that the disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 33 publications
7
42
0
Order By: Relevance
“…This suggests that self-discovery metaphors relate to well-being, even when they are applied to close others. This provides some indication (consistent with Schlegel et al, 2012) that self-discovery beliefs are a marker of (or can help foster) positive psychological functioning.…”
Section: Resultssupporting
confidence: 65%
See 4 more Smart Citations
“…This suggests that self-discovery metaphors relate to well-being, even when they are applied to close others. This provides some indication (consistent with Schlegel et al, 2012) that self-discovery beliefs are a marker of (or can help foster) positive psychological functioning.…”
Section: Resultssupporting
confidence: 65%
“…Previous work on self-discovery metaphors has found that endorsing the idea that true selves are discovered (in general) positively predicts meaning in life judgments (Schlegel et al, 2012). Thus, we conducted exploratory correlation analyses to examine the relationship between discovery beliefs, change evaluation, and three well-being measures (meaning in life, selfesteem, and satisfaction with life).…”
Section: Studymentioning
confidence: 96%
See 3 more Smart Citations